Strategi pengukuran upaya berbahasa menerusi kesantunan berbahasa sebagai indikator profesionalisme guru pelatih berasaskan skala morfofonetik, sosiolinguistik dan sosiopragmatik (Linguistic politeness as an indicator of trainee teacher professionalism: a language ability measurement strategi based on morphophoetic, sociolinguistc and sociopragmatic scales) - Mohamed Redzwan, Husna Faredza; Bahari, Khairul Azam; Sarudin, Anida; Osman, Zulkifli (Universiti Utara Malaysia Press, 2019)
Purpose - The aim of this study was to identify Malaysian trainee teachers’ language ability through their use of high and cultured Malay language (HCML) as a politeness feature, as measured by morphophonetic, sociolinguistic and sociopragmatic scales in a Trainee Teacher Professionalism Indicator. Methodology - Respondents were nine Malay language trainee teachers from five selected secondary schools in the state of Perak.A qualitative approach was used to gain in-depth understanding of their HCML ability. A teaching observation and facilitation checklist incorporating morphophonetic, sociolinguistic and sociopragmatic scales was developed based on Brown and Levinson’s (1987) conceptual framework. Data was collected during classroom observations of the nine trainee teachers. Recordings of these sessions totalling 540 minutes were transcribed and analysed.Findings - The study found some disregard for morphophonetic aspects of language use, especially in articulating particular words in standard Malay pronunciation. There was also evidence of inattention to sociolinguistic rules, i.e., looseness due to code mixing. These non-adherence issues should be addressed in an appropriate manner so that both the language ability and level of professionalism of trainee teachers can be enhanced. In the sociopragmatic aspect, however, all 15 linguistic politeness sub-strategies of Brown and Levinson’s Positive Politeness Strategy (1987) were found to be practiced, indicating that the teacher trainees’ language ability was positive, and fulfilled the professionalism indicator. Significance - This study contributes towards the development of a teacher professionalism indicator for trainee teachers in the researchers’ own institution and elsewhere from the perspective of HCML ability, that may be used to evaluate linguistic politeness during teaching practice, especially among Malay language trainee teachers.